Study of Mangrove Ecosystem Potential in Management as Ecoturism Area in Teling Village, Tombariri District, Minahasa Regency, North Sulawesi Province - Rolley M.E.F. Pesik; Adnan S. Wantasen; Febri S.I. Menajang; Anthonius P. Rumengan; Noldy G.F. Mamangkey; Joice R.T.S.L. Rimper; Deiske A. Sumilat; Joshian N.W. Schaduw (JURNAL PESISIR DAN LAUT TROPIS, 2025)
The purpose of this study is to analyze the potential conditions of the mangrove ecosystem, land suitability, conditions and perceptions of the Teling village community to be developed as an ecotourism area. The survey of the potential of the mangrove ecosystem used the transect-quadrant method, while the potential for socio-economic conditions, infrastructure and perceptions of the Teling village community was carried out using the interview method. There are 6 (six) types of mangroves found in Teling Village, namely Avicennia officinalis, Bruguiera gymnorrhiza, Rhizophora mucronata, Sonneratia alba and Sonneratia caseolaris. The mangrove species with the highest average density value is R. mucronata at 33.33 individuals/300m², the highest average frequency value is found in the B. gymnorrhiza and R. stylosa species, which is 0.89, the highest average cover value is found in the S. alba species, which is 1.0265 m2/300 m2, the highest average Importance Value Index (INP) is found in the Rhizophora mucronata species, which is 111.0 with the "moderate" category, the average mangrove diversity index of Teling village is 2.66 with the "moderate" category, while the average mangrove evenness index is 0.693 with the "moderate" category. The mangrove tourism suitability index of Teling village is 2.5, which means that this area is "very suitable". Keywords: ecotourism, mangrove, Teling Village ABSTRAK Tujuan dari penelitian ini adalah menganalisa potensi kondisi ekosistem mangrove, kesesuaian lahan, kondisi dan persepsi masyarakat Desa Teling untuk dikembangkan sebagai kawasan ekowisata. Survei potensi ekosistem mangrove menggunakan metode transek-kuadran, sedangkan potensi kondisi sosial ekonomi, infrastruktur dan persepsi masyarakat desa Teling melalui metode wawancara dan pengisian lembar kuisioner. Ada 6 (enam) jenis mangrove yang ditemukan di Desa Teling yaitu Avicennia officinalis, Bruguiera gymnorrhiza, Rhizophora mucronata, Sonneratia alba dan Sonneratia caseolaris. Jenis mangrove dengan nilai rata-rata kepadatan jenis tertinggi adalah Rhizophora mucronata sebesar 33,33 individu/300m², nilai rata-rata frekuensi jenis tertinggi terdapat pada jenis B. gymnorrhiza dan R. stylosa yaitu sebesar 0,89, nilai rata-rata penutupan jenis tertinggi terdapat pada jenis Sonneratia alba yaitu 1,0265 m2/300 m2, rata-rata Indeks Nilai Penting (INP) tertinggi pada jenis Rhizophora mucronata yaitu 111,0 dengan kategori “sedang”, rata-rata indeks keanekaragaman mangrove desa Teling sebesar 2,66 dengan kategori “sedang”, sedangkan rata-rata indeks kemerataan mangrove-nya yaitu 0,693 dengan kategori “sedang”. Indeks kesesuaian wisata mangrove desa Teling adalah 2,5 yang artinya kawasan ini “sangat sesuai” untuk dikembangkan sebagai kawasan ekowisata mangrove. Kata kunci: ekowisata, mangrove, Desa Teling